2013
DOI: 10.1158/1078-0432.ccr-13-0238
|View full text |Cite
|
Sign up to set email alerts
|

Colon Cancer–Specific Cytochrome P450 2W1 Converts Duocarmycin Analogues into Potent Tumor Cytotoxins

Abstract: Purpose: Cytochrome P450 2W1 (CYP2W1) is a monooxygenase detected in 30% of colon cancers, whereas its expression in nontransformed adult tissues is absent, rendering it a tumor-specific drug target for development of novel colon cancer chemotherapy. Previously, we have identified duocarmycin synthetic derivatives as CYP2W1 substrates. In this study, we investigated whether two of these compounds, ICT2705 and ICT2706, could be activated by CYP2W1 into potent antitumor agents.Experimental Design: The cytotoxic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 25 publications
2
51
0
Order By: Relevance
“…Certain isoforms, notably CYP1A1, 1B1 and 3A4 are identified as highly expressed in certain tumours 10 indicating the value of truncated azinomycin analogues as potential bioprecursors with chemotherapeutic efficacy. We have demonstrated proof of principle with bioprecursors of the duocarmycin natural products targeting CYP1A1 19,20 and 2W1 14,21 enzymes. Uniquely, we have demonstrated that CYP selective bioactivation in vivo can be obtained with no overt toxicity to normal tissues including the liver.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Certain isoforms, notably CYP1A1, 1B1 and 3A4 are identified as highly expressed in certain tumours 10 indicating the value of truncated azinomycin analogues as potential bioprecursors with chemotherapeutic efficacy. We have demonstrated proof of principle with bioprecursors of the duocarmycin natural products targeting CYP1A1 19,20 and 2W1 14,21 enzymes. Uniquely, we have demonstrated that CYP selective bioactivation in vivo can be obtained with no overt toxicity to normal tissues including the liver.…”
Section: Discussionmentioning
confidence: 98%
“…Uniquely, we have demonstrated that CYP selective bioactivation in vivo can be obtained with no overt toxicity to normal tissues including the liver. 13,14 Further development of such a bioprecursor approach could provide a strategy to exploit the azinomycins for therapeutic use. While CYP1A1 and 1B1 provide selective cancer drug targets, the hepatic CYP3A4 enzyme could be exploited for liver specific treatment of hepatitis B, hepatitis C and hepatocellular carcinoma 22 or with the reemergence of the oncolytic virus, a 'suicide' GDEPT approach also exists as a therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also appeared that the cytotoxic metabolite of chloromethylindolines can be transferred from one tumor cell to others in close proximity, thus indicating a bystander propagating effect (Sheldrake et al, 2013;Travica et al, 2013).…”
Section: Cyp2w1 As a Target For Colon Cancer Therapymentioning
confidence: 99%
“…Given their importance,p articularly in xenobiotic and drugm etabolism, [1] ag reat deal of research has been conducted into their roles, the identification of their sequences, and their catalytic mechanisms. [2][3][4] Whilst an umber of CYPs, particularly human liver CYPs and extrahepatic CYPs (i.e.,C YP1A1, CYP1B1, and CYP2W1)h ave been the subjecto f intense investigation, [5][6][7] there is stillm uch to be learnt from these mixed-function oxidases. This reflects the difficulties associated with studyingt hese enzymes,because:1 )they are encoded by large gene families, and their functions cannotb e predicted fromt heir gene sequence;2 )they are difficult to assay,i solate and purify, so classical biochemical methods are often ineffective in identifying enzymes of interest;3 )these proteins are membrane bound and often depend on co-enzymes and cofactors, making them difficult to express as functional enzymesi nc ellular systems; and 4) polymorphismsa nd epigenetic regulationa lter their expression levels and functional activity.T herefore, new approaches to identifying, evaluating, and quantifyingf unctionally active CYPs are of utmost importance.…”
mentioning
confidence: 99%